Effects of Glucosamine in the Temporomandibular Joint Osteoarthritis: A Review - Sivakumar, Sasidharan; Sivakumar, Gowardhan; Sundramoorthy, Ashok K. (Current Rheumatology Reviews, 2024)
Osteoarthritis in the temporomandibular joint (TMJ) is a chronic disease characterized by irreversible damage to articular surfaces, including inflammation, loss of articular cartilage, and subchondral bone alterations, which would be radiographically evident only in later stages. Symptomatic slow-acting so-called nutraceutical drugs have been proposed as a treatment for osteoarthritis in comparison to non-steroidal anti-inflammatory drugs (NSAID) because of their appreciable safety profile even in long-term intake. Glucosamine, being one among them, proved highly efficient in knee osteoarthritis. However, its application in TMJ osteoarthritis dates back only to 2001 and is still inconclusive in its efficiency even with systematic reviews, in restoring the structural and functional aspects of damaged TMJ. Glucosamine, being a natural compound and also a contributor to building the matrix of articular cartilage, can be utilized effectively for TMJ osteoarthritis as an adjunct along with other conventional treatment modalities available till now, which also have moderate prognosis in most of the clinical scenarios. This review summarizes data relating to the mechanism of osteoarthritis and its management using glucosamine formulations. The beneficial effects of glucosamine on the pathophysiology of TMJ osteoarthritis are possibly due to its contribution to hyaluronic acid regulation and in establishing a proper balance between anabolism/catabolism in the articular tissues.
Keywords: cartilage